2014
DOI: 10.1016/j.cja.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Dihedral influence on lateral–directional dynamic stability on large aspect ratio tailless flying wing aircraft

Abstract: The influence of dihedral layout on lateral-directional dynamic stability of the tailless flying wing aircraft is discussed in this paper. A tailless flying wing aircraft with a large aspect ratio is selected as the object of study, and the dihedral angle along the spanwise sections is divided into three segments. The influence of dihedral layouts is studied. Based on the stability derivatives calculated by the vortex lattice method code, the linearized small-disturbance equations of the lateral modes are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Conventional tail has a less directional stability and it is likely to induce spiral instability which caused the roll and yaw motion to be slightly decreased due to damping effect cause by vertical tailplane . Referring to aerodynamic principal which indicates the changes in dihedral angle can alter the angle of attack along span wise tail section while aircraft in sideslip mode, this leads to change in lift distribution along span wise section of the tail which altered the lateral directional aerodynamic derivatives [12]. The non-linear response of Conventional tail configuration is starts at sideslip angle, 15 • due to the stall of vertical tail (rudder) as shown in Figure 6(a).…”
Section: A Reynolds Sweep Testmentioning
confidence: 96%
“…Conventional tail has a less directional stability and it is likely to induce spiral instability which caused the roll and yaw motion to be slightly decreased due to damping effect cause by vertical tailplane . Referring to aerodynamic principal which indicates the changes in dihedral angle can alter the angle of attack along span wise tail section while aircraft in sideslip mode, this leads to change in lift distribution along span wise section of the tail which altered the lateral directional aerodynamic derivatives [12]. The non-linear response of Conventional tail configuration is starts at sideslip angle, 15 • due to the stall of vertical tail (rudder) as shown in Figure 6(a).…”
Section: A Reynolds Sweep Testmentioning
confidence: 96%
“…Generally, profile drag could be reduced by adding winglets at the tip of an airplane's wing [10]. Previous studies have demonstrated that an increased dihedral angle could reduce the coefficient of drag (C D ) in a pigeon model [11], and the increased anhedral angle could also reduce the C D [12], causing these angles to stabilize in the lateral direction while flying [11,13]. Based upon these previous studies and our observations, we could speculate that synergistic pectoral fin flexion (θ F and φ R ) in Mobula japanica would be relevant in different roles: the flexion angle of the root joint of the pectoral fin (φ R ) mainly controls posture in the pitch direction, and the flexion angle of the pectoral fin (θ F ) may have fine-tuned postural maneuverability.…”
Section: B Effect Of Combined Changes In θ F and φ R On Velocity Dismentioning
confidence: 99%
“…However, in aviation history before the stability augment system was invented, several aircrafts with flying wing configurations such as Ho.229 and N-9M appeared which have no vertical stabilizer to provide enough directional static stability. On the other hand, it has been proven that the lateral-directional stability of this configuration can be achieved by adjusting the spanwise dihedral layout without installing a stability augment system [15,16]. Instead of focusing on the required lateral-directional stability derivative C lβ or C nβ , a criterion of dynamic stability was included in the aerodynamic design for flying wing, which considered the Dutch roll mode characteristics as the critical element for flight qualities [17].…”
Section: Introductionmentioning
confidence: 99%